Bone Loss around Dental Implants 5 Years after Implantation of Biphasic Calcium Phosphate (HAp/βTCP) Granules. (5th December 2018) - Klimecs, Vadims; Grishulonoks, Alexanders; Salma, Ilze; Neimane, Laura; Locs, Janis; Saurina, Eva; Skagers, Andrejs
Abstract : Biphasic calcium phosphate ceramic granules (0.5–1.0 mm) with a hydroxyapatite and β -tricalcium phosphate ratio of 90/10 were used. Biphasic calcium phosphate ceramic granules produced in the Riga Technical University, Riga Rudolph Cimdins Biomaterials Innovation and Development Centre, were used for filling the bone loss on 18 patients with peri-implantitis. After 5 years at the minimum, clinical and 3D cone-beam computed tomography control was done. Clinical situation confirmed good stability of implants without any signs of inflammation around. Radiodensity of the previous gap and alveolar bone horizontally from middle point of dental implants showed similar radiodensity as in normal alveolar bone. This trial is registered with ISRCTN13514478.